Appraisal of the Ethiopian Legal Environment in Light of Its Compatibility for Introduction of Electronic Bill of Lading - Israel Woldekidan Haileyesus (Journal of International Trade, Logistics and Law, 2020)
Bill of lading is playing vital role in international commercial transaction. In terms of development it has been used in forms of paper until recent time. Due to the advent of technology and the inherent problems associated with being used in forms of paper results introduction of dematerialized bill of lading in the maritime industry. It is not abundantly used by the maritime community for reason mainly attributed to lack of uniform international law governing such dematerialized bill of lading. Ethiopia has tendency towards introduction of electronic bill of lading. However, there are concerns regarding compatibility of Ethiopian laws to accommodate digitalize bill of lading. This paper looks into legal concerns of introducing electronic bill of lading and the existing Ethiopia legal environment in light of its room for accommodating electronic bill of lading and it revealed that the law has gaps to address the legal concerns associated with EBL.